Measuring the effectiveness of Integrated Marketing Communication (IMC) on real estate business : a study on Concord Real Estate Ltd. - Alam, Md. Mahbub (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration,2013.